Assessing academic anxiety in d/Deaf, DeafBlind, and hard of hearing individuals - Pizzie, Rachel Gabriella; Kim, Christina Eun-Young; Sortino, Rachel Marie; Inghram, Rachel (Frontiers in Psychology, 2026)
Students encounter many challenges to academic success. Whereas some students thrive in stressful environments, other students falter. Some students also encounter social and emotional factors that might detract from academic achievement, including negative emotions like stress and anxiety. Academic anxieties refer to negativity, nervousness, and avoidance associated with different academic domains, such as math anxiety, science anxiety, test anxiety, trait (general) anxiety, and writing anxiety. Not only do individuals with high academic anxiety experience stress, but high academic anxiety is associated with decreased academic performance in the specific domain. On average, d/Deaf, DeafBlind, and hard of hearing (DDBHH) people show decreased academic performance compared to hearing populations, but more research is needed to understand how academic anxieties may play a role in creating challenges for DDBHH students. In the present study, we explored the reliability of the Academic Anxiety Inventory (AAI) in a DDBHH sample (N = 145). In this study, each AAI item was presented in both American Sign Language (ASL) and English, providing additional accessibility to DDBHH participants. Results showed that each of the five subscales of the AAI had high reliability. Moreover, a factor analysis showed each of the hypothesized five subscales of the AAI were represented by corresponding factors in this sample. In this DDBHH sample, the AAI showed relatively low intercorrelation between domains of anxiety, demonstrating that the domains of anxiety are relatively independent and separable from one another. Additional results compared the DDBHH with a sample of hearing people from the original psychometric validation of the AAI and explored other relations between the AAI and language background. Overall, these results suggest that the AAI is a reliable and appropriate questionnaire for use with DDBHH participants. Understanding and addressing academic anxieties in DDBHH communities is a priority for encouraging academic achievement. Developing appropriate, culturally sensitive, and accessible ways to reduce the impact of these anxieties is vital to encourage DDBHH students to achieve their potential.